Determination of Biochemical Contents of Fresh, Oven-Dried, and Sun-Dried Peels and Pulps of Five Apple Cultivars (Amasya, Braeburn, Golden Delicious, Granny Smith, and Starking) - Zeynep Ergün (Journal of Food Quality)
This study aimed to investigate the biochemical compounds of five different apple cultivars (Amasya, Braeburn, Golden Delicious, Granny Smith, and Starking) grown in the same location and to reveal the differences between peel and pulp in the fresh, oven-dried, and sun-dried samples. Sugar and organic acid contents were analyzed through high-performance liquid chromatography. Besides, antioxidant activity, total flavonoid, and total phenolic contents were analyzed with a spectrophotometer. The results of these analyses showed that the compounds varied between peel and pulp and among fresh, oven-dried, and sun-dried samples. The largest level of total flavonoid was found in Amasya oven-dried peel, and the largest total phenol, antioxidant activity, fructose, and total sugar levels were observed in Amasya sun-dried peel. Moreover, the largest L-ascorbic acid was detected in Amasya oven-dried pulp. Granny Smith oven-dried pulp was rich in citric, succinic acids, and glucose. Braeburn sun-dried pulp, Golden Delicious oven-dried pulp, and Granny Smith sun-dried pulp contained the largest sucrose, malic acid, and total soluble solids levels, respectively. For data interpretation, t-test, ANOVA, Duncan’s test, Kruskal–Wallis H test, and principal component analysis were performed. The peel contained significantly higher total flavonoid, total phenol, and antioxidant activity than pulp. Moreover, among fresh, oven-dried, and sun-dried samples, total phenol, succinic acid, malic acid, and L-ascorbic acid significantly differed. As a whole, the pulp was rich in sugars. The results provide valuable information on the food quality parameters of five different apple cultivars. It was demonstrated that consuming apple with its peel is healthier (in terms of total flavonoid, total phenol, antioxidant activity parameters, and L-ascorbic acid), and drying (especially the sun-drying method) is an effective food storage method for apples.